2007
DOI: 10.1007/s00464-007-9330-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring new technologies to facilitate laparoscopic surgery: creating intestinal anastomoses without sutures or staples, using a radio-frequency-energy-driven bipolar fusion device

Abstract: Introduction: Intestinal anastomotic healing requires apposition of the collagencontaining submucosal layers of the opposing intestinal walls, which is traditionallyachieved by staples or sutures. Recently, a feedbackcontrolled bipolar sealingsystem (LigaSure) has been successfully introduced to seal and transect vessels.Since this technology depends on fusion of collagen fibres which are abundantlypresent in the intestinal wall, the possibility to create intestinal anastomoses usingthis technology was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 19 publications
4
42
0
1
Order By: Relevance
“…From this point of view, a similar closure was considered to be possible also in the intestine. In their anastomosis study on four pigs, Smulders et al (11) created eight anastomoses with the prototype tool they had developed themselves by using LigaSure only (11). It was seen that the pigs were healthy for seven days.…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, a similar closure was considered to be possible also in the intestine. In their anastomosis study on four pigs, Smulders et al (11) created eight anastomoses with the prototype tool they had developed themselves by using LigaSure only (11). It was seen that the pigs were healthy for seven days.…”
Section: Discussionmentioning
confidence: 99%
“…At the highest power setting, we found slightly less thermal injury caused by the Harmonic scalpel (127.48 lm) than LigaSure (144.18 lm), but that difference was nonsignificant. Certain studies, e.g., Diamantis et al; Sutton et al [26,28] in their studies, found that LigaSure (197.79 lm) might cause less thermal injury than Harmonic scalpel (205.61 lm) but that difference was not significant. Sartori and colleagues [18] found that the only real advantage between LigaSure and Harmonic scalpel was a shorter duration of surgery with the Harmonic scalpel, probably owing to its ability to coagulate and cut at the same time.…”
Section: Thermal Damage In Laparoscopy-an In-depth Reviewmentioning
confidence: 94%
“…The device applies a precise amount of mechanical pressure and radiofrequency energy to tissue, causing fusion of the opposing layers by creating a seal of denatured collagen, which can then be transected [28,29]. The superiority of LigaSure over bipolar electrocautery is that the tissue fusion is created by the denaturation of proteins, thus forming a true seal rather than creating a proximal thrombus.…”
Section: Thermal Damage In Laparoscopy-an In-depth Reviewmentioning
confidence: 99%
“…This device applies a precise amount of mechanical pressure and radiofrequency energy to tissue, causing fusion of the opposing layers by creating a seal of denatured collagen, which can be transected 7 . The superiority of LigaSure TM is that the tissue fusion is created by the denaturation of proteins, thus forming a true seal rather than creation of a proximal thrombus.…”
Section: Introductionmentioning
confidence: 99%
“…Because collagen is abundantly present in intestinal wall, we assumed that the device would have been capable of creating intestinal walls seals, and would have had enabled secure appendectomy 7 .…”
Section: Introductionmentioning
confidence: 99%